Developing grounded theory : the second generation revisited - Morse, Janice M. (New York : Routledge, 2021)
"Grounded theory is the most popular genre of qualitative research used in the health professions and is widely used elsewhere in the research world. In this volume, six key grounded theory methodologists examine the history, principles, and practices of this method, highlighting areas in which different strands of the methods diverge. Chapters cover the work of Anselm Strauss, Barney Glaser, Leonard Schatzman, and the postmodern and constructivist schools. This volume will be ideal for courses on grounded theory that wish to show the ways in which it can be used in research studies"--
Revised edition of Developing grounded theory, c2009.
OCLC-licensed vendor bibliographic record.
Keywords: Research methods -- Congresses; Grounded theory -- Congresses; Qualitative research -- Congresses; PSYCHOLOGY / Research & Methodology; SOCIAL SCIENCE / Research